The development of the legal framework governing the Shari'ah committee of the Islamic banking and takaful institutions in Malaysia - Hussain, Mohammad Azam (Islamic Business School, 2016)
In Malaysia, the Sharῑᶜah Committee established by Islamic banks and takāful operators are subject to the legal framework as set out by the legislations governing Islamic financial services. The legal framework of the Sharῑᶜah committee existed since the enforcement of Islamic Banking Act 1983 (Act 276) in year 1983. Since that, improvements have been made by the government to strengthen such legal framework via a series of legal amendments as well as the introduction of new legislations. Apart from that, the Sharῑᶜah Committee is also governed by the Guidelines issued by Central Bank of Malaysia to ensure sustainability of Islamic banking and takāful industry in Malaysia. This article adopted historical and comparative methods in order to analyse the development of the legal framework governing the Sharῑᶜah Committee of the Islamic banking and takāful institutions in Malaysia. The study found that the legal framework of the Sharῑᶜah Committee is mainly governed by Islamic Financial Services Act 2013 (Act 759) and Sharῑᶜah Governance Framework for Islamic Financial Institutions (CBM/RH/GL 012-3).